Taiwan Photon Source Delivers its Design Target with a Stored Current of 520 mA. Issue 3 (3rd May 2016) - Lin, Diana
Abstract : After several months of upgrade work in the second phase of commissioning, the 3 GeV Taiwan Photon Source (TPS) of the National Synchrotron Radiation Research Center (NSRRC) successfully stored 520 mA of electron current, exceeding its design goal of 500 mA, in its storage ring on December 12, 2015. It is less than a year since the first light was achieved in the TPS store ring by using two room-temperature, five-cell PETRA radio frequency (RF) cavities.